PENGARUH PROFITABILITAS, STRUKTUR AKTIVA, PERTUMBUHAN PENJUALAN DAN LIKUIDITAS TERHADAP STRUKTUR MODAL (Perusahaan Subsektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2015-2019) - Mutiara Putri Astiana (JURNAL ILMIAH EDUNOMIKA, 2021)
The researchhwas conducted to test whether there is anneffect of profitability (Return OnnAssets), asset structure, salesggrowth and liquidity (CurrentrRatio) on the capital structure (Debt tooEquity Ratio) in food anddbeverage sub-sector companiesslisted on theeIndonesia Stock Exchange (IDX) from 2015-2019. This type of research is descriptiveqquantitative with appopulation of 26ccompanies and the sample used is 10 companies usinggpurposiveesampling method and obsevations for 5 years so that 50 observationalddata are obtained. Secondary data were obtained from the officialwwebsite of the IndonesiasStock Exchange. The analysis technique uses multiple linier regression analysis with the SPSS 15 program. Based on the resultsoof theeanalysis, it can be concluded that profitability anddliquidity have a signicanteeffect on capital structure, while assetsstructure and salesggrowth has noosignificant effectoon capitalsstructure. Keywords: ROA. Asset structure, Sales growth. CR, DER